PENDAMPINGAN DALAM PEMBERDAYAAN TANAH WAKAF DESA PUTAT LOR - Muyassaroh; M. Saiful Islam (Jurnal Aksi Afirmasi, 2021)
This community service is carried out in the form of Islamic philanthropy which focuses on legalizing and empowering waqf land. The legalized waqf land is in the form of non-productive waqf as well as several prayer rooms (musala) located in the area of Putat Lor village, Krajan, Gondanglegi, in Malang district. This waqf is trying to be assisted in the legalization process by carrying out the three-stage of "heir waqf" method. This method includes observing data on the heirs whom the land being handed over, validating the heirs’ agreement, and implementing the waqf pledge. This process is carried out within three weeks.